Using rotation measure to search for magnetic fields around galaxies at z 0.5. Issue Volume 11:Issue S321(2015) (21st March 2017) - Williams, Anna; Lundgren, Britt; Mao, Sui Ann; Wilcots, Eric; Zweibel, Ellen
Abstract: Magnetic fields are an important component in galaxies, and yet, we still do not know how these magnetic fields were originally seeded within galaxies, nor how they have grown to the strengths we observe today. One way we can unravel this complex problem is by measuring the growth of magnetic fields over cosmic time. We present the initial results of a rotation measure study to search for the presence of coherent magnetic fields around young disk-like galaxies at z 0.5. The S-band receiver at the VLA allows us to simultaneously observe Stokes I, Q, U, and V from 2-4 GHz. With these broadband polarization observations we apply multiple methods for determining the rotation measure of each source, improving the fidelity of our results. Beyond magnetogenesis, the results of this study also have implications for the life-cycle of baryons within galaxies and the composition of galactic haloes.